Challenges and Opportunities for School Principals in Innovating at SMTK Kanaan Jaya-Jayapura - Bu'tu, Dorce -; Mulde, Deysi Olvie (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This research aims to explore the challenges and opportunities faced by the principal's leadership in increasing innovation at SMTK Kanaan Jaya, Jayapura Regency. Using qualitative methods with a phenomenological approach, this study delves into the first-hand experiences of school principals, teachers, and students in facing various obstacles and taking advantage of opportunities to encourage innovation in the educational environment. This phenomenological approach allows for a comprehensive analysis of the principal's leadership transformation through direct observation, in-depth interviews, and documentation of policies implemented in schools. The data collected was analyzed using the Miles and Huberman method, which included the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that school principals face challenges from within and from outside, but also find opportunities, namely policies that are in line with the demands of development that can support the principal's innovation program